Terrible angels : semantic ambivalence and polysemy - Smirnova, Alexandra; Tolochin, Igor (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study deals with the problem of ambivalence at the semantic level of word meaning. We argue that semantic ambivalence determines the whole structure of polysemy of certain English words and propose a method of establishing contextual markers indicating the presence of semantic ambivalence as the essential element of word meaning. Having studied a large variety of contexts for the word ‘angel’, we have identified three typical collocational patterns of its use in texts. Therefore, we suggest that this word has three main senses that are distinguished by their evaluative properties: ambivalent, positive and negative. In the ambivalent type of context ‘angel’ collocates with both positively and negatively charged words at the same time, which creates verbal sequences of high emotional tension. This fact proves the idea that certain words in the English language can convey simultaneously positive and negative aspects of human experience in a particular type of their usage as intrinsically inseparable from each other. Ambivalent word senses are referred to as archetypes, for they represent the legacy of the archaic syncretism of the human mind, which has been handed down to us in religion and poetry. Most modern monolingual English dictionaries do not take into account the distinction in the evaluative characteristics of collocational patterns when defining the word ‘angel’. This leads to a number of problems in their lexicographic descriptions of this word. Taking into account its semantic ambivalence would contribute to a more coherent picture of its sense structure.